Penerapan Model Pembelajaran AIR untuk Meningkatkan Hasil Belajar Siswa Kelas V SDN 15 Pangkajene - St Maryam M; Nur Ilmi; Nurhikmah Mansur (STKIP Andi Matappa Pangkep, 2023)
The problem in this research is the low learning outcomes in mathematics subjects for class V students based on results of observations. This research aims to determine the process and outcomes of student learning the application of the AIR learning model data presentation material for class V students at SDN 15 Pangkajene. The approach used in this research is a qualitative approach where the results obtained are described in the form of narrative text with a type of classroom action research to improve the quality of the learning process. The research results in cycle I, teacher activities classified sufficient (C), student activities classified sufficient (C) and student learning outcomes classified sufficient (C). In cycle II, by making improvements to existing deficiencies there is an increase in the data obtained so that teacher activities are classified good (B), student activities are classified good (B) and student learning outcomes is classified good (B). The conclusion of the research is that applying the AIR learning model can improve the process and results of mathematics learning in data presentation material for class V students at UPT SDN15 Pangkajene Sidrap Regency.